2017
DOI: 10.1016/j.drugalcdep.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

“Don’t think I’m going to leave you over it”: Accounts of changing hepatitis C status among couples who inject drugs

Abstract: a b s t r a c tBackground: While the health-related benefits of intimate partnership are well documented, little attention has been paid to couples exposed to high levels of social stigma and exclusion. In this project we investigated an important site of stigma for partnerships by collecting accounts of changing hepatitis C (HCV) status ("sero-change") among couples that inject drugs. We explored what these accounts reveal about the meaning of HCV for these couples, and how this understanding contributes to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…Those who had a partner who used drugs were more likely to reduce their injecting frequency, a reduction difference of more than nine injections a week. This finding was surprising, as previous literature associated having a partner who uses drugs, in particular those injecting, with increased frequency of injecting and of sharing of injecting equipment . A variety of papers have been published on the power imbalance and social inequalities that drive injecting risk behaviour in heterosexual couples, in particular in women who inject drugs, who often rely on their male partner to acquire, prepare and inject the drugs .…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Those who had a partner who used drugs were more likely to reduce their injecting frequency, a reduction difference of more than nine injections a week. This finding was surprising, as previous literature associated having a partner who uses drugs, in particular those injecting, with increased frequency of injecting and of sharing of injecting equipment . A variety of papers have been published on the power imbalance and social inequalities that drive injecting risk behaviour in heterosexual couples, in particular in women who inject drugs, who often rely on their male partner to acquire, prepare and inject the drugs .…”
Section: Discussionmentioning
confidence: 93%
“…A variety of papers have been published on the power imbalance and social inequalities that drive injecting risk behaviour in heterosexual couples, in particular in women who inject drugs, who often rely on their male partner to acquire, prepare and inject the drugs . Disregard of injecting risk occurs as a consequence of emotional closeness, intimacy, trust and commitment . Given the high level of sero‐concordance in people who inject drugs in intimate partnerships, the study team identified patients in dyadic intimate partnerships who had both been enrolled on the Eradicate‐C trial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations